TiO2/Activated carbon photo cathode catalyst exposed to ultraviolet radiation to enhance the efficacy of integrated microbial fuel cell-membrane bioreactor. (September 2019) - Bhowmick, G.D.; Chakraborty, I.; Ghangrekar, M.M.; Mitra, A.
Abstract: Two integrated microbial fuel cell-membrane bioreactor (MFC-MBR) were developed to treat medium-strength wastewater with simultaneous power generation. Both the systems were operated with photo-sensitized cathode (with TiO2 -Activated carbon) with one irradiated by UV-A light (MMT-UV), while the other was not in direct contact with any light sensitization (MMT). In polarization, MMT-UV exhibited higher maximum power density of 494 mW m −2 as compared to MMT (239 mW m −2 ). Normalized energy recovery was also estimated to be 0.122 kWh m −3 for MMT-UV and 0.058 kWh m −3 for MMT. On the other hand, overall chemical oxygen demand and total Kjeldahl nitrogen removal efficiency were almost similar and high enough ( ̴ 95% and 86–90%, respectively) for these type of two-stage wastewater treatment systems with very less footprint. Hence, the integrated MFC-MBR with TiO2 -Activated carbon as cathode-catalyst in presence of UV showed excellent treatability of wastewater with simultaneous bioelectricity generation to reduce the overall energy demand. Graphical abstract: Unlabelled Image Highlights: Integrated MFC-MBR system with TiO2 as photo electro-catalyst was investigated. Overall COD removal efficiency of this system was found to be around 95%. MFC-MBR system in presence of UV exhibited higher maximum power density. Normalized energy recovery was found to be 0.122 kWh m −3 in presence of UV.